Pengaruh Literasi Digital terhadap Pelaksanaan Asuhan Keperawatan - Lestari Hernawati; Rr. Tutik Sri Hariyati (Journal of Telenursing (JOTING), 2023)
This literature study aims to describe the influence of digital transformation on the implementation of nursing care in terms of ethics and the side of providing nursing care. The method used is an integrated literature review method where the source of information is obtained from searching various journals published from 2016 to 2021. Journal searches using the words "nursing care", "digital literacy" and "digital transformation". The results of the research after After reviewing six related articles, the main theme was how nurses take advantage of technological developments in implementing digital health literacy, and the benefits felt by nurses. In conclusion, digital nursing technology really helps nurses in providing nursing care to clients where their time becomes more efficient. and the quality of services has increased, but this has also led to a process of dehumanization as a result of technology, so it is necessary to develop an attitude of digital professionalism as an effort to build a professional identity that can maintain human values in providing patient-centered nursing care. Key words: Nursing care; digital literacy; digital transformation